The Effect of Privatization on the Egyptian Banking Sector - Albadawi, Sara (Université d'Ottawa | University of Ottawa, 2014)
Egypt has experienced different stages of development over the course of its economic evolution. In the 1950s and 1960s, the government nationalized several enterprises across Egypt, bringing them under state ownership and control. Nationalization proved to be unsuccessful because it did not solve the underlying economic problems, namely slow growth and huge deficits. Later, in the early 1990s, Egypt introduced liberalization and privatization as a step towards becoming a free-market economy. This paper conducts a thorough literature review on the impact of the privatization reform on the Egyptian economy. More specifically, this paper analyzes the impact on the Egyptian banking sector of privatization and of the banking reform plan adopted by the Central Bank of Egypt. Furthermore, this paper considers the effect of the global financial crisis and of the 2011 revolution on the Egyptian banking sector